2020
DOI: 10.1016/j.outlook.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Social support and clinical improvement in COVID-19 positive patients in China

Abstract: Highlights Most COVID-19 positive inpatients had sleep, depressive, and anxiety symptoms. Both physical and psychological symptoms significantly improved after clinical and psychosocial intervention. Female, severe pneumonia, worse social support and more relatives infected were associated with the symptomatology. Effective social support, improvement from COVID-19 and higher educational level predicted the psychological improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 29 publications
(38 reference statements)
2
74
0
4
Order By: Relevance
“…Women may be more likely to have sleep problem, depressive symptom [26], and more intrusive flashbacks as they were more sensitivity to emotional stimuli and resulted in altered immune function and hormone level [25,27]. We also found that unmarried respondents were more likely to suffer higher pressure.…”
Section: Plos Onementioning
confidence: 56%
See 1 more Smart Citation
“…Women may be more likely to have sleep problem, depressive symptom [26], and more intrusive flashbacks as they were more sensitivity to emotional stimuli and resulted in altered immune function and hormone level [25,27]. We also found that unmarried respondents were more likely to suffer higher pressure.…”
Section: Plos Onementioning
confidence: 56%
“…This result was consistent with the previous study, which also found that female may be associated with the worse psychological status during COVID-19 epidemic [ 24 , 25 ]. Women may be more likely to have sleep problem, depressive symptom [ 26 ], and more intrusive flashbacks as they were more sensitivity to emotional stimuli and resulted in altered immune function and hormone level [ 25 , 27 ]. We also found that unmarried respondents were more likely to suffer higher pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience, adaptive coping strategies and social support have been linked to better mental health performing during the pandemic [ 50 ]. Psychosocial interventions have been shown to be especially useful in reducing loneliness [ 51 ] and anxiety during the pandemic [ 52 ], in reducing alcohol consumption [ 53 ], and even improving physical health [ 54 ]. Finally, the fact of maintaining and healthy daily routines, as well as avoiding alcohol consumption are useful general recommendations in both genders as these behaviors showed a protective effect on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes were promoted by psychological interventions based on social support, psychological rehabilitation, and psychoeducation. The model of social support may have been particularly useful, such as some studies highlighted [ 51 , 52 ], because the service had to address problems that arose or were exacerbated during a moment of widespread social isolation [ 51 ]. At the same time, it showed its worth in answering the questions that many users were asking regarding the management of problems linked to the reference system (children, partner, etc.).…”
Section: Resultsmentioning
confidence: 99%